The Elongator subunit Elp3 is a non-canonical tRNA acetyltransferase - Lin, Ting-Yu (Nat Commun, 2019)
The Elongator complex catalyzes posttranscriptional tRNA modifications by attaching carboxy-methyl (cm(5)) moieties to uridine bases located in the wobble position. The catalytic subunit Elp3 is highly conserved and harbors two individual subdomains, a radical S-adenosyl methionine (rSAM) and a lysine acetyltransferase (KAT) domain. The details of its modification reaction cycle and particularly the substrate specificity of its KAT domain remain elusive. Here, we present the co-crystal structure of bacterial Elp3 (DmcElp3) bound to an acetyl-CoA analog and compare it to the structure of a monomeric archaeal Elp3 from Methanocaldococcus infernus (MinElp3). Furthermore, we identify crucial active site residues, confirm the importance of the extended N-terminus for substrate recognition and uncover the specific induction of acetyl-CoA hydrolysis by different tRNA species. In summary, our results establish the clinically relevant Elongator subunit as a non-canonical acetyltransferase and genuine tRNA modification enzyme.